Therapeutic properties of Moringa oleífera Lam. in the treatment of diabetes mellitus - Andrade, José Isaac Alves (2020)
The Moringa oleifera is a species of perennial plant, native to the western and southern Himalayas and northeast India. Its nutritional and phytochemical richness has been the target of several studies, as they have relevant therapeutic effects, such as anticancer, antiallergic, anti-inflammatory, immunomodulatory, antifungal, antibacterial, hepatoprotective and antidiabetic. In this context, the present study aimed to explain the therapeutic potential of oil Moringa in the treatment of diabetes mellitus. For this, a systematic search was carried out in the PubMed, ScienceDirect and SciELO databases. For the search, the following descriptors were used: Moringa oleifera; Diabetes Mellitus and Hypoglycemic Drugs. All selected from the Health Sciences Descriptors (DeCS) and used in the languages: Portuguese and English. At first, 501 publications were found and after applying the predetermined inclusion and exclusion criteria, 18 pertinent publications remained, which served as the basis for the construction of the work. It was observed that Moringa oleífera has, among numerous benefits, important hypoglycemic activity, an action attributed, above all, to the abundance of nutrients and secondary metabolites capable of positively influencing serum glucose levels. For example, some bioactive compounds such as isothiocyanates, quercetin, gallic acid, ellagic acid and chlorogenic acid, are cited as relevant hypoglycemic agents, as they are able to inhibit enzymes related to carbohydrate degradation in the gastrointestinal tract. In addition to these metabolites, Moringa oleífera contains protein fractions similar to insulin, which in addition to controlling blood glucose levels and improving oral tolerance, has greater stability and activity time in the body. It has also been shown that Moringa oleífera has been used as a therapeutic alternative, not only in the control of diabetes itself, but also in the treatment of diseases associated with this pathology, such as diabetic nephropathy, oxidative stress, impaired healing, endothelial dysfunction and cardiovascular diseases. In addition, the literature suggests that this species has no significant toxicity. Thus, it can be concluded that Moringa oleifera proved to be important on hyperglycemia, as well as on the damage caused by it. However, the use of this plant as a therapeutic resource for diabetes is not yet recommended, given the scarcity of studies that demonstrate its effects on humans.